Synthesis and study of a novel 9P-type mixed layered tetradymite-like GeBi4Te4 compound in the Ge-Te-Bi system - Aliyev, F.R. (Physics and Chemistry of Solid State, 2021)
Taking as a base structural properties of the tetradymite-like layered chalcogenide compounds, a novel ternary GeBi4Te4 phase was predicted and synthesized. The polycrystal of this compound was synthesized and its single-crystal was grown by the vertical Brigman-Stokbarger method. The phase composition of obtained samples was analyzed by differential thermal analysis (DTA), X-ray powder diffraction (XRD), and scanning electron microscope (SEM). It was determined that the novel phase melts peritectially at 538 °C and has the following lattice parameter values in a hexagonal configuration: a=4,4071(6)Å, c=17,384(2)Å (sp. gr P3m1). This crystal structure is considered a derivative of tetradymite-like layered chalcogenides and consists of alternating Bi bilayers and GeBi2Te4 septuple packets.